Leadership competencies and the uncertainties of blockchain adoption in the public sector - Haq, Syed Hammad Ul; Dan, Sorin; Shahzad, Khuram (Edward Elgar, 2026)
Public sector organizations are digitally transforming through emerging and disruptive technologies such as blockchain, with accompanying uncertainties. For successful digital transformation and addressing the associated uncertainties with these technologies, leaders and managers require competencies. This chapter focuses on the set of leadership competencies required for addressing uncertainties associated with blockchain technology using a sensemaking framework. Sensemaking as a framework allows leaders to structure unknown issues and foresee the uncertainties posed by blockchain adoption. Through sensemaking, leaders first identify cues regarding the uncertainties of blockchain, interpret these cues into meaningful narratives during the second step, and then enact accordingly. Our findings show that leaders can overcome uncertainties through the sensemaking framework. Qualitative data were collected through 13 semi-structured interviews with 11 public sector organizations in Finland across different sectors. To complement the interviews, secondary data from webpages, reports, and openly available data about the organizations were utilized.
Keywords: digital transformation; leadership competencies; sensemaking; blockchain; public sector; fi=Julkisjohtaminen|en=Public Management|; fi=Julkisjohtaminen|en=Public Management|; fi=Tuotantotalous kaupp|en=Industrial Management econ|